Strategi Pengembangan Obyek Wisata Pantai di Kabupaten Gunungkidul - Pramono, Aditya; Dwimawanti, Ida Hayu (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Research Strategy Development of Beach Tourism in Gunungkidul Regency is descriptive qualitative research. This research uses strategic management to disclose emerging issues intensively and comprehensively. This study aims to determine what efforts have been made to improve and maximize existing resources to be used in developing beach tourism and any obstacles that arise in the beach attractions of Gunungkidul Regency. The focus of this research is on the strategy of improving the tourism sector especially beach tourism, thus using SWOT analysis as the main instrument to measure the environment and obtain the strategy of the strengths, weaknesses, opportunities and threats required in the process of planing development and developing beach tourism. The conclusion of this research is based on beach tourism development strategy in Gunungkidul Regency conducted by Tourism Office of Gunungkidul Regency, there are still indicators that have not yet succeeded, seen in the uneven distribution of development in some excellent destinations and still not the presence of foreign tourists who come to visit. Then the authors want to provide a strategy recommendation to improve the strategy that has not been successful with SWOT analysis and existing Litmus Tests.